2018
DOI: 10.1002/bkcs.11467
|View full text |Cite
|
Sign up to set email alerts
|

Towards Versatile Continuous‐Flow Chemistry and Process Technology Via New Conceptual Microreactor Systems

Abstract: In the past decade, microreaction technology has been attracted much attention to the scientific community as one of the subareas in chemical synthesis. The microreactor improves the yield with higher selectivity, and also facilitates the reactions by simple, safe, fast, and green approaches. This review gives an overview on our contributions to develop versatile continuous-flow syntheses and process technology by exampling gas-liquid binary phase in modified PDMS microreactors, and process intensification for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 129 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Continuous‐flow microreactors have recently attracted much attention as an important technique for synthesizing organic molecules including drug intermediates/molecules in a very short time under mild reaction conditions A high surface area to volume ratio in this microfluidic system promotes mass and heat transfer, leading to selectivity and conversion much superior to the levels obtainable by conventional batch processes . Owing to their many complex issues such as inefficient mixing, non‐uniformity in heat, and safety in the scale‐up of batch process, in recently, flow approach is more attractive and reliable in both academia and industry , .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continuous‐flow microreactors have recently attracted much attention as an important technique for synthesizing organic molecules including drug intermediates/molecules in a very short time under mild reaction conditions A high surface area to volume ratio in this microfluidic system promotes mass and heat transfer, leading to selectivity and conversion much superior to the levels obtainable by conventional batch processes . Owing to their many complex issues such as inefficient mixing, non‐uniformity in heat, and safety in the scale‐up of batch process, in recently, flow approach is more attractive and reliable in both academia and industry , .…”
Section: Methodsmentioning
confidence: 99%
“…From all these experiments, it was observed that the reaction time could surprisingly be decreased to 3.93 s from 5 min in flask (Table , entry 3) at a total flow rate of 3 mL/min to attain the identical chemical performance of the desired product 3 in 67 % yield and the side products 4 & 5 in 5 % & 21 %, respectively, which is consistent with the results of the reaction in flask (entry 8, Table ). Notably, the use of larger diameter PFA capillary (1.0 mm) significantly decreased the yield of product 3 (52 %), presumably owing to lowered mixing efficiency, (Table , entry 7). Excellent mixing efficiency throughout the confined reaction space of the microfluidic reactor, which is provided by a high surface‐area‐to‐volume ratio, lowered the synthesis time to several seconds (3.9 s) from several minutes (5 min).…”
Section: Methodsmentioning
confidence: 99%
“…Flow chemistry as a branch of organic synthesis has been reviewed extensively through several informative and educational articles [14][15][16][17][18][19][20][21] and books [22][23][24][25][26][27]. As such our aim is not to include a comprehensive review here but to simply highlight the principle characteristics and direct the reader to the listed references for further consultation.…”
Section: The Advantages Of a Flow Approachmentioning
confidence: 99%
“…[9,14] Kim and co-workersd eveloped ad ual-channel microreactor strategy for performingg as-liquid transformations ( Figure 1b). [15] The microreactor is fitted with ah ydrophobic poly(dimethylsiloxane) (PDMS)m embrane (45 mmt hickness) which allowsd iffusion of gases but is impermeablet ot he other reaction components. Ag as flows along one channel passing through the membrane into the second channel containing the liquid phase for the organic transformation.T he system was first reported for reactions involving O 2 .…”
Section: Conventional Approaches For Handling Gasesmentioning
confidence: 99%
“…Kim and co‐workers developed a dual‐channel microreactor strategy for performing gas–liquid transformations (Figure b) . The microreactor is fitted with a hydrophobic poly(dimethylsiloxane) (PDMS) membrane (45 μm thickness) which allows diffusion of gases but is impermeable to the other reaction components.…”
Section: Gas–liquid Membrane Microreactorsmentioning
confidence: 99%